Pemanfaatan Aplikasi Mendeley sebagai Sistem Manajer Referensi Digital untuk Penulisan Karya Ilmiah bagi Guru Bahasa Arab di Banten - Zainal Rafli; Samsi Setiadi; Puti Zulharby (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2021)
Background: Citation cannot be separated from scientific work. The initial survey results show that most teachers who are members of the Arabic Subject Teacher Consultation in Banten still do not understand how to write good scientific papers, including how to cite and create a bibliography or reference automatically. Mendeley is a citation management application that is free or open-source, user-friendly, has an attractive appearance, and can be used on online and offline devices. For this reason, community service activities and collaborations for teachers at Banten need to be held so that teachers can receive training in using Mendeley to manage scientific documents. Methods: Partner participation is carried out with a training program within one day. The technique used is workshop, mentoring and evaluation. Workshop activities to introduce applications, benefits and how Mendeley works, then video tutorials on installation on laptop devices are given. Results: This service activity resulted in 1) 90% of teachers getting additional knowledge and insight regarding the use of the Mendeley application as a digital reference management system for writing scientific papers, 2) providing training to teachers on the technical use of the Mendeley application as a digital reference management system for writing works scientifically. Conclusion: Through this training, 90% of teachers at the Banten can use the Mendeley application to support scientific article writing and encourage the productivity of each teacher to write scientific articles.